In Silico Assessment of Drug-Like Properties of Phytocannabinoids in Cannabis Sativa - Desa, Shakinaz; Osman, Asiah; Hyslop, Richard (EDUCATUM Journal of Science, Mathematics and Technology, 2017)
This study investigated drug-like properties of phytocannabinoids in Cannabis sativa using an in silico study. We report sixteen phytocannabinoids: cannabidiol (CBD), cannabidiolic acid (CBDA), cannabinol (CBN), cannabichromene (CBC), cannabigerol (CBG), cannabicyclol (CBL), cannabivarin (CBV), cannabidivarin (CBDV), cannabichromevarin (CBCV), cannabigerovarin (CBGV), cannabinodiol (CBDL), cannabielsoin (CBE), cannabitriol (CBT), Δ9-tetrahydrocannabinol (Δ9-THC), Δ9-tetrahydrocannabivarin (Δ9-THCV), and Δ8-tetrahydrocannabinol (Δ8-THC). All chemical structures and properties were obtained from PubChem Compound, National Center for Biotechnology Information,U.S. National Library of Medicine. Molinspiration was used for the calculation of molecular properties and bioactivity score. The parameters were molecular weight (MW), number of hydrogen acceptor (HBA), number of hydrogen donor (HBD), partition coefficient (cLogP), polar surface area (PSA) and number of rotatable bonds (NROTB). We predicted bioactivity scores for G Protein-Coupled Receptors (GPCR) ligand, ion channel modulator, kinase inhibitor, nuclear receptor ligand, protease inhibitor and enzyme inhibitor. Lipinski’s rule was used as reference to determine the drug-like properties of the phytocannabinoids. All compounds have MW<500, HBA<10, HBD<5, TPSA<140Å2 and NRTOB<10. Bioactivity score showed an active or moderately active in all compounds. Fifteen compounds were detected to have one violation. CBT did not violate any of the Lipinski’s Ro5 and demonstrated as a good drug-like property and for oral absorption. This suggests that CBT can be further tested for potential orally active drugs.